2009
DOI: 10.1121/1.3058632
|View full text |Cite
|
Sign up to set email alerts
|

The eigenspectra of Indian musical drums

Abstract: In a family of drums used in the Indian subcontinent, the circular drum head is made of material of non-uniform density. Remarkably, and in contrast to a circular membrane of uniform density, the low eigenmodes of the non-uniform membrane are harmonic. In this work we model the drum head by a non-uniform membrane whose density varies smoothly between two prescribed values. Using a Fourier-Chebyshev spectral collocation method we obtain the eigenmodes and eigenvalues of the drum head. For a suitable choice of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The drum head is modeled as a nonuniform membrane with a density that varies smoothly, and its eigenmodes and eigenfrequencies are calculated using the proposed numerical method. The numerical method used in this section is the same as that applied in previous work [5]. However, in the previous work, the parametric study of the number of grid points was insufficient, and therefore we explore the relation between the number of grid points and the accuracy of the proposed numerical method in more detail, particularly by making an aspect of comparison with experimental data.…”
Section: Application Of a Spectral Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The drum head is modeled as a nonuniform membrane with a density that varies smoothly, and its eigenmodes and eigenfrequencies are calculated using the proposed numerical method. The numerical method used in this section is the same as that applied in previous work [5]. However, in the previous work, the parametric study of the number of grid points was insufficient, and therefore we explore the relation between the number of grid points and the accuracy of the proposed numerical method in more detail, particularly by making an aspect of comparison with experimental data.…”
Section: Application Of a Spectral Methodsmentioning
confidence: 99%
“…As referred to in the Introduction, it is acknowledged that using spectral collocation methods offers the greatest accuracy for the least computational expense in this class of problem [5]. Thus, we adopt a Fourier-Chebyshev spectral collocation technique [8] to numerically analyze the wave equation for a nonuniform membrane.…”
Section: Application Of a Spectral Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indian drums, especially tablas are very well studied in terms of the additional paste applied to their drum head [8] [7] called sihai which is placed concentric for the dayan and off-centric for the bayan drum. Varying the width, position, smoothness and strength of the sihai it was found that the harmonic overtone relations of the drum modes change and can meet values very close to harmonic ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Physical models of the drum have been performed for Indian drum heads [8], the snare drum [2], or the bass drum [1]. Basic models of viscoelastic damping have mainly been discussed with Finite-Element Methods [13].…”
Section: Introductionmentioning
confidence: 99%